Book Reviews - Rines, Lawrence S.; Lewis, Thomas T.; Welborn, Robert H.; Romer, K. Gird; Williams, James C.; Trollinger, William Vance; Selcer, Richard; Means, Richard L.; Mohr, Clarence L.; Odom, E. Dale; Vaughn, William Preston; Frey, Marsha; et al. (Teaching History: A Journal of Methods, 1986)
A. K. Dickinson, P. J. Lee, and P. J. Rogers. Learning History. London: Heinemann Educational Books, Ltd., 1984. Pp. x, 230. Paper, $14.00; Donald W. Whisenhunt. A Student's Introduction to History. Boston: American Press, 1984. Pp. 31. Paper, $2.95. Review by Robert A. Calvert of Texas A&M University. Ronald J. Grele. Envelopes of Sound: The Art of Oral History. Chicago: Precendent Publishing, Inc. 1985. Second Edition. Pp. xii, 283. Cloth, $20.95. Review by Marsha Frey of Kansas State University. Reginald Horsman. The Diplomacy of the New Republic, 1776-1815. Arlington Heights, Illinois: Harlan Davidson., 1985. Pp. vii, 153. Paper, $7.95. Review by William Preston Vaughn of North Texas State University. Lynn Y. Weiner. From Working Girl to Working Mother: The Female Labor Force in the United States, 1820-1980. Chapel Hill and London: The University of North Carolina Press, 1985. Pp. xii, 187. Cloth, $17.95. Review by E. Dale Odom of North Texas State University. Mary Custis Lee de Butts, ed. Growing Up in the 1850s: The Journal of Agnes Lee. Chapel Hill and London: University of North Carolina Press, 1984. Pp. xx, 151. Cloth, $11.95. Review by Clarence L. Mohr of Tulane University. Raymond A. Mohl. The New City: Urban America in the Inudstrial Age, 1860-1920. Arlington Heights, Illinois: Harlan Davidson, Inc., 1985. Pp. 242. Paper, $8.95; Melvyn Dubofsky. Industrialism and the American Worker, 1865-1920 (Second Edition). Arlington Heights, Illinois: Harlan Davidson, Inc., 1985. Pp. 167. Paper, $8.95. Review by Richard L. Means of Mountain View College. David D. Lee. Sergeant York: An American Hero. Lexington, Kentucky: University Press of Kentucky, 1985. Pp. 162. Cloth, $18.00. Review by Richard Selcer of Mountain View College. Studs Terkel. "The Good War": An Oral History of World War Two. New York: Pantheon Books, 1984. Pp. xv, 589. Cloth, $19.95. Review by William Vance Trollinger of The School of the Ozarks. David W. Reinhard. The Republican Right Since 1945. Lexington: The University Press of Kentucky, 1983. Pp. ix, 294. Cloth, $25.00. Review by James C. Williams of Gavilan College. Christina Larner. Witchcraft and Religion: The Politics of Popular Belief. New York: Basil Blackwell, 1984. Pp. xi, 172. Cloth, $24.95. Review by K. Gird Romer of Kennesaw College. F. R. H. DuBoulay. Germany in the Later Middle Ages. New York: St. Martin's Press, Inc., 1984. Pp. xii, 260. Cloth, $30.00; Joseph Dahmus. Seven Decisive Battles of the Middle Ages. Chicago: Nelson Hall, 1984. Pp. viii, 244. Cloth, $23.95. Review by Robert H. Welborn of Clayton College. Gerald Fleming. Hitler and the Final Solution. With an Introduction by Saul Friedlaender. Berkeley: University of California Press, 1984 (German, 1982). Pp. xxxvi, 219. Cloth, $15.95; Sarah Gordon. Hitler, Germans, and the "Jewish Question." Princeton: Princeton University Press, 1984. Pp. xiv, 412. Cloth, $40.00; Limited Paper Edition, $14.50. Review by Thomas T. Lewis of Mount Senario College. Alan Cassels. Fascist Italy. Arlington Heights, Illinois: Harlan Davidson, Inc., 1985. Second Edition. Pp. x, 146. Paper, $8.95. Review by Lawrence S. Rines of Quincy Junior College; Additional response by Lawrence S. Rines of Quincy Junior College.